Comparison of different thermal comfort models: mosque and church cases - Atmaca, Ahmet Bircan; Gedik, Guelay Zorer; Wagner, Andreas; Schweiker, Marcel (TAYLOR & FRANCIS LTD, 2024)
The abbreviated summary is below: Many thermal comfort models are based on the subjective perception of the users in the buildings. The models are created within some limitations and scope. This study aims to contribute to the development of thermal comfort models by comparing the widely used and being developed thermal comfort models with users' actual votes in natural settings. Thermal comfort models were evaluated on the most used religious buildings cases, and suggestions were made for the design and use of religious buildings. For these purposes, thermal comfort measurements were conducted at different zones of prayer areas in churches and mosques in Karlsruhe, Germany. After the events with high participation, a thermal sensation survey was performed on the users. The data were analyzed statistically. According to the results, there are differences between comfort models according to user perception. However, the results of aPMV and ATHB models are closer to user perception than PMV model.
Keywords: Thermal comfort; religious building; adaptive comfort; PMV; aPMV; ATHB; BUILDINGS; SENSATION; Architecture